Passiflora edulis leaf extract inhibits inflammatory response and preserves intestinal barrier function in Caco-2 and RAW264.7 co-culture model - CARMO, Mônica Cristina Lopes do; MARTINS, Isabela Mateus; MAGALHÃES, Ana Elisa Ramos; CHIOCCHETTI, Gabriela de Matuoka e; MARÓSTICA JÚNIOR, Mário Roberto MARÓSTICA JÚNIOR; MACEDO, Juliana Alves (Food Science and Technology, 2023)
Inflammatory bowel disease (IBD) is a chronic and incurable illness that affects people all over the world. Conventional therapies usually cause adverse side effects that may affect patients’ quality of life. This study assessed the effect of the aqueous extract of Passiflora edulis leaves (PELE) in co-culture of Caco-2 and RAW264.7 cells, simulating an in vitro model of IBD. After being stimulated with bacterial-derived lipopolysaccharides (LPS), PELE’s treatment inhibited the release of the pro-inflammatory cytokines interleukin (IL) 6 and 8, although was not able to reduce nitric oxide (NO) production. In the co-culture system, PELE was also able to preserve the intestinal barrier function by decreasing paracellular permeability and increasing transepithelial electrical resistance (TEER) values, compromised after the LPS stimulus. The beneficial activity seen in this in vitro study may suggest that PELE has a possible anti-inflammatory role in IBD and can alleviate inflammatory events.